Osteoclasts degrade fibrinogen scaffolds and induce mesenchymal stem/stromal osteogenic differentiation. Issue 4 (24th December 2019) - Almeida, Ana R.; Bessa‐Gonçalves, Mafalda; Vasconcelos, Daniel M.; Barbosa, Mário A.; Santos, Susana G.
Abstract: Fibrinogen (Fg) is a pro‐inflammatory protein with pro‐healing properties. Previous work showed that fibrinogen 3D scaffolds (Fg‐3D) promote bone regeneration, but the cellular players were not identified. Osteoclasts are bone resorbing cells that promote bone remodeling in close crosstalk with osteoblasts. Herein, the capacity of osteoclasts differentiated on Fg‐3D to degrade the scaffolds and promote osteoblast differentiation was evaluated in vitro. Fg‐3D scaffolds were prepared by freeze‐drying and osteoclasts were differentiated from primary human peripheral blood monocytes. Results obtained showed osteoclasts expressing the enzymes cathepsin K and tartrate resistant acid phosphatase colonizing Fg‐3D scaffolds. Osteoclasts were able to significantly degrade Fg‐3D, reducing the scaffold's area, and increasing D‐dimer concentration, a Fg degradation product, in their culture media. Osteoclast conditioned media from the first week of differentiation promoted significantly stronger human primary mesenchymal stem/stromal cell (MSC) osteogenic differentiation, evaluated by alkaline phosphatase activity. Moreover, week 1 osteoclast conditioned media promoted earlier MSC osteogenic differentiation, than chemical osteogenesis inductors. TGF‐β1 was found increased in osteoclast conditioned media from week 1, when compared to week 3 of differentiation. Taken together, our results suggest that osteoclasts are able to differentiate and degrade Fg‐3D, producing factors like TGF‐β1 that promote MSC osteogenic differentiation.